Complex pathways for young mothers outside employment, education and training. Issue 1 (2nd January 2016) - Russell, Lisa
Abstract : This article explores young mothers' experiences of turbulent pathways in and out of education and work in Northern England. Data are drawn from an ethnography conducted between 2010 and 2013 that incorporated participant observation, life-story maps, photographs and interviews carried out in young mothers' homes, parenting classes and employment-based education and training programmes. These particular young women were sometimes directed into inappropriate education and training courses based on their 'young unemployed mother' status rather than encouraged to embark upon an individualised pathway relevant to their particular needs and career aspirations. Pathways are explored using Bourdieu's concept of capital to expose how these women expressed agency and navigated their own way through the different and sometimes competing fields of education, family and work.